Racial and ethnic differences in individual-level and area-based socioeconomic status and 12-month DSM-IV mental disorders. (December 2019) - Chen, Ruijia; Kessler, Ronald C.; Sadikova, Ekaterina; NeMoyer, Amanda; Sampson, Nancy A.; Alvarez, Kiara; Vilsaint, Corrie L.; Green, Jennifer Greif; McLaughlin, Katie A.; Jackson, James S.; Alegría, Margarita; Williams, David R.
Abstract: The purpose of this study was to: (1) examine the associations of individual-level objective socioeconomic status (OSS), subjective socioeconomic status (SSS), and area-based indicators of socioeconomic status, with 12-month DSM-IV mood, anxiety, alcohol use, and drug use disorders; and, (2) determine the extent of racial/ethnic differences in these associations across non-Latino White, non-Latino Black, Latino, and Asian participants. Data are from the Collaborative Psychiatric Epidemiology Studies dataset, a collection of three population-based surveys of mental disorders among U.S. residents aged 18 and older (n = 13, 775). Among all indicators of socioeconomic status, SSS was most consistently associated with 12-month mental disorders. Income was negatively associated with mood and anxiety disorders; education was negatively associated with alcohol use and drug use disorders. Significant interactions with race/ethnicity were found for the associations of socioeconomic indicators with anxiety, alcohol use, and drug use disorders but not with mood disorders. SSS was not associated with any of the 12-month mental disorders among Blacks. Education had stronger associations with 12-month anxiety and alcohol use disorders among Whites than among other racial/ethnic groups. Among Asians, low income compared to high income was associated with a lower risk of anxiety disorders and less than high school completion compared to college or more was associated with a lower risk of alcohol use disorders. Finally, tract-level income inequality was associated with a greater risk of drug use disorders only among Blacks. The patterns and magnitudes of the associations of individual-level and area-based socioeconomic indicators differed by type of disorder and race/ethnicity.